Influências do orçamento público na produção científica: um estudo sobre a ação orçamentária de fomento para pesquisa na rede federal de educação profissional, científica e tecnológica - Estevam, Célia Aparecida Almeida (2024)
The Federal Network for Professional, Scientific and Technological Education is considered a bold initiative in Brazilian educational policy, standing out for the creation and transformation of federal institutions into Federal Institutes that play a fundamental role in consolidating the teaching, research and extension tripod. This network is maintained with public funds from the federal government. In this context, the following hypotheses are formulated: a) the allocation of specific budget resources for research allows for the allocation of part of the discretionary federal budget to finance expenses related to scientific production; and b) there is potential growth in the scientific production of teachers at the Network's institutions, driven by the institution's financial support and favorable conditions for carrying out research. The main objective of this study is to investigate the budget management of the Research Promotion Action and its influence on academic production, considering the articles published by teachers. To this end, the aim is to map the allocation of financial resources by the Federal Network, evaluate the evolution of budget allocations over time and invent the articles published by permanent and active teachers, identifying authors, characteristics, citations and the network of co-authorships of researchers benefiting from researcher aid between 2018 and 2022. The research adopted a methodological strategy that integrated bibliographic and documentary methods with bibliometric analysis, organized into three distinct phases and using a method triangulation approach to provide a comprehensive view of the study. In the exploratory phase, qualitative methods were used to understand the phenomena studied and establish a solid theoretical basis, reviewing the literature on Science, Technology and Society, Public Choice Theory, Actor-Network Theory and Public Budgeting. The descriptive phase focused on collecting and analyzing budget data from the Federal Network, using the Integrated Planning and Budgeting System and the Transparency Portal to examine the amounts allocated and committed, with an emphasis on the Research Promotion Action. In the final phase, the empirical data was organized and analyzed to correlate the funding of research activities with scientific production, considering the articles published by teachers at the Federal Institute of Minas Gerais, which was selected because it had the highest amounts allocated and committed to Action 6380/21B3. The data analyzed indicates that, despite progress, research in the Network still faces significant challenges, such as budget limitations and administrative decisions that impact the allocation of resources to finance expenses directly linked to research activities. The application of the Actor-Network Theory and the Public Choice Theory made it possible to understand that the effectiveness of funding policies is directly related to the interaction between managers, teachers and the resources available, which is essential for boosting the impact of these institutions on the scientific scene. Finally, the results obtained highlight the effectiveness of researcher support as an instrument for promoting research, suggesting that the strategic allocation of resources can boost research activities and consolidate the position of the Federal Institutes as important research and innovation hubs. It is believed that initiatives such as this research can contribute to the continuity of the dialog and bring about paradigm shifts in the Network's institutions, taking advantage of the legal flexibility of budget allocation, which is discretionary for each management, to promote investments in research activities.